1997
DOI: 10.1046/j.1365-2303.1997.43175431.x
|View full text |Cite
|
Sign up to set email alerts
|

A study to determine the underlying reason for abnormal glandular cytology and the formulation of a management protocol

Abstract: A retrospective review is presented of 89 patients with glandular dyskaryosis in order to formulate a management protocol. Fifteen patients had cervical intraepithelial neoplasia (CIN) without glandular abnormality (17%). One patient had adenocarcinoma in situ of the cervix and one patient had vaginal intraepithelial neoplasia (VAIN) grade III. Twenty-two patients had endometrial carcinoma (24.5%) and 11 patients had cervical carcinoma (12.5%). Of the patients presenting with post-menopausal bleeding as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…However, due to its relative rarity, the management of CGIN varies from LLETZ and CKC to SH. Following the diagnosis of CGIN on a cervical smear the clinician is committed to examination of the whole of the transformation zone/endocervical canal 24 . In our study, of the 14 patients who had colposcopically directed punch biopsy, 13 went on to have either CKC or LLETZ.…”
Section: Discussionmentioning
confidence: 96%
“…However, due to its relative rarity, the management of CGIN varies from LLETZ and CKC to SH. Following the diagnosis of CGIN on a cervical smear the clinician is committed to examination of the whole of the transformation zone/endocervical canal 24 . In our study, of the 14 patients who had colposcopically directed punch biopsy, 13 went on to have either CKC or LLETZ.…”
Section: Discussionmentioning
confidence: 96%
“…Based on the NHSCSP ‘ABC’ publication 4 , the abnormal glandular cytology of this study is of borderline category and not of glandular neoplastic category, the latter representing definite glandular dyskaryosis. Leeson et al 5 found, on review of 89 women with glandular dyskaryosis, 22 endometrial cancers (24.7%), 11 cervical cancers (12.3%), 15 cases of cervical intraepithelial neoplasia (16.8%), one adenocarcinoma in situ , and one vaginal intraepithelial neoplasia. The average age of this group was 54.3 years and approximately one‐third presented with postmenopausal bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…The predictive value of abnormal glandular cytology is compromised by several factors. Firstly, the positive predictive value, for preneoplastic and neoplastic pathology, of smears showing a high‐grade glandular cytologic abnormality varies between 17% and 95.7% (31,42–45) . Secondly, the occurrence of benign conditions that mimic cervical glandular neoplasia cytologically (46) .…”
Section: Management Of Cervical Glandular Abnormalitiesmentioning
confidence: 99%